Improved intestinal absorption of paclitaxel by mixed micelles self-assembled from vitamin E succinate-based amphiphilic polymers and their transcellular transport mechanism and intracellular trafficking routes - Xiaoyou Qu; Yang Zou; Chuyu He; Yuanhang Zhou; Yao Jin; Yunqiang Deng; Ziqi Wang; Xinru Li; Yanxia Zhou; Yan Liu (Taylor & Francis Group, 2018)
To ensure that antitumor drugs can be effectively transported across intestinal barrier and then quickly released in tumor cells, mixed polymeric micelles (Mix-PMs) were designed and fabricated by combining poly(2-ethyl-2-oxazoline)-vitamin E succinate (PEOz-VES) with TPGS1000 for enhancing intestinal absorption of paclitaxel. PEOz-VES exhibited an extremely low critical micelle concentration and negligible cytotoxicity. The Mix-PMs were characterized to have about 20 nm in diameter, uniform spherical morphology, high drug-loading content and sustained drug release profile with a retained pH-sensitivity. The results of the transport through Caco-2 cell monolayers and intestinal absorption revealed that Mix-PMs displayed higher transcellular transport efficiency compared with PEOz-VES micelles and Taxol®. The possible mechanism of transcellular transport for Mix-PMs was elucidated to be mainly through clathrin- and caveolae/lipid rafts-mediated transcytosis. Confocal laser scanning micrographs revealed that late endosomes, lysosomes, endoplasmic reticulum, Golgi apparatus, and mitochondria were all involved in intracellular trafficking of Mix-PMs. The proteins involved in transcytosis of Mix-PMs and finally excreted were unraveled for the first time by the analysis of proteins in the basolateral media according to the proteomics method. Consequently, the fabricated mixed polymeric micelles may have great potential in enhancing intestinal absorption and accelerating drug release in tumor cells.